Exposure Assessments for Children in Homes and in Daycare Centers to NO2, PMs and Black Carbon - 이재영; 김창혁; 김종범; 류성희; 배귀남 (Asian Journal of Atmospheric Environment, 2018)
Indoor air quality was investigated in homes and daycares located in areas with heavy traffic in Seoul, South Korea from November 2013 to January 2014. Indoor and outdoor air quality measurements were collected for 48 hours in four children’s homes and daycare centers. The I/O ratio (Indoor to outdoor ratio) for each major air pollutant (NO2, black carbon, PM10, and PM2.5) was calculated, and NO2 and PM10 concentration profiles were analyzed based on indoor activity diaries recorded during the 48 hours. Most I/O ratios for NO2, black carbon, PM10, and PM2.5 at daycare centers were less than one. At homes, I/O ratios for black carbon, PM10, and PM2.5 were less than one; however, most I/O ratios for NO2 were greater than one due to the usage of gas stoves. The children’s exposure to indoor air pollutants was calculated using a time-weighted average exposure method, and the daily intake level for each pollutant was determined.
Keywords: Indoor air quality; Air pollutants; Children; I/O ratio; Exposure assessment